Godless : the church of liberalism - Coulter, Ann H. frey50 (New York : Crown Forum, 2006)
Argues that in spite of declarations from liberals that they are not religious, liberalism has its own set of beliefs that display many attributes commonly found in religion.
On the Seventh Day, God Rested and Liberals Schemed -- The Passion of the Liberal: Thou Shalt Not Punish the Perp -- The Martyr: Willie Horton -- The Holiest Sacrament: Abortion -- Liberals' Doctrine of Infallibility: Sobbing Hysterical Women -- The Liberal Priesthood: Spare the Rod, Spoil the Teacher -- The Left's War on Science: Burning Books to Advance "Science" -- The Creation Myth: On the Sixth Day, God Created Fruit Flies -- Proof for How the Walkman Evolved into the iPod by Random Mutation -- The Scientific Method of Stoning and Burning -- The Aped Crusader.
Keywords: USA -- Regierung; Liberalism -- United States; Liberalismus; United States -- Politics and government -- 1989-